Pola Konsumsi Pangan Pokok dan Kontribusinya Terhadap Tingkat Kecukupan Energi Masyarakat Desa Sukadamai - As Syaffa Amalia Adha; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Consumption of staple foods as a source of carbohydrates contributes the largest energy for body.Food consumption pattern needs to be considered because it affects the nutritional status of thecommunity and the nutrient adequacy ratio. The nutrient adequacy ratio can be known by lookingat the frequency and amount of individual meals in a day. The study aims to determine contributionof staple foods for nutrient adequacy ratio of the Sukadamai Village community. The study wasconducted on March 17, 2020 in Sukadamai Village, Bogor Regency. The number of respondents asmany as eight people are people who live in the village of Sukadamai. Data collection techniques inthis study used the Semi Quantitative Food Frequency Questionnaire (SQFFQ) method throughdirect interviews. Most people still rely on rice as the staple food with frequency of eating twice aday. The total energy intake in meeting the greatest nutritional needs is sourced from rice. Most ofrespondents have low contribution of staple food which is insufficient to meet the nutrient adequacyratio.